Burnout among English language teachers of urban and rural secondary schools in Kuantan, Pahang Darul Makmur / Amira Abdul Jalil - Abdul Jalil, Amira (Faculty of Education, 2014)
The study was conducted to investigate the levels of burnout among English language teachers of secondary schools in urban and rural area. It intends to examine the different levels of burnout experiencing by English language teachers of secondary schools in urban and rural area, factors that lead to the burnout as well as the coping strategies to overcome burnout. A total of 20 English teachers of secondary schools in urban area and 20 English language teachers of secondary schools in rural area in Kuantan are involved in this study. A survey research method was used. The result of the study suggests that there is not much difference in the levels of burnout experienced by English language teachers in urban and rural secondary schools. The factor of work overload is the most contributing factor that leads to burnout of the English teachers in urban area. Meanwhile, the factor of work environment is the most contributing factor that leads to burnout of English teachers in rural area. The most effective coping strategies to overcome burnout for English teachers in urban and rural area are by going for holiday as well as by spending more time in doing things they like. The least effective coping strategy to overcome burnout is by being optimistic on challenges faced. Suggestions on how to overcome factors that lead to burnout are mentioned in this study such as by lessening teachers' workload, limiting scope of duties for teachers and also teachers should fully utilize school's facilities and ESL materials provided by the school.